2007
DOI: 10.1029/2007gl030502
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between optical, chemical and physical properties of biomass burn aerosols

Abstract: [1] Aerosols generated from burning different plant fuels were characterized to determine relationships between chemical, optical and physical properties. Single scattering albedo (w) and Angstrom absorption coefficients (a ap ) were measured using a photoacoustic technique combined with a reciprocal nephelometer. Carbon-to-oxygen atomic ratios, sp 2 hybridization, elemental composition and morphology of individual particles were measured using scanning transmission X-ray microscopy coupled with near-edge X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
88
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 25 publications
(32 reference statements)
11
88
1
1
Order By: Relevance
“…Variations in chemical composition for ponderosa pine, chamise, and palmetto wood smokes, as determined by AMS measurements, are consistent with a classification proposed by Hopkins et al (2007a) based on X-ray and electron microscopy measurements. That work reported three major particle-type categories based on chemical and optical properties: (1) materials composed of liquid/oily organic carbon (OC) and BC with no inorganic inclusions (e.g., ponderosa pine combustion particles), (2) non-homogenous mixture of carbonaceous and inorganic materials (e.g., palmetto combustion particles), and (3) BC material with fractal morphology typical of soot containing inorganic inclusions (e.g., chamise combustion particles).…”
Section: Composition and Morphologysupporting
confidence: 84%
See 2 more Smart Citations
“…Variations in chemical composition for ponderosa pine, chamise, and palmetto wood smokes, as determined by AMS measurements, are consistent with a classification proposed by Hopkins et al (2007a) based on X-ray and electron microscopy measurements. That work reported three major particle-type categories based on chemical and optical properties: (1) materials composed of liquid/oily organic carbon (OC) and BC with no inorganic inclusions (e.g., ponderosa pine combustion particles), (2) non-homogenous mixture of carbonaceous and inorganic materials (e.g., palmetto combustion particles), and (3) BC material with fractal morphology typical of soot containing inorganic inclusions (e.g., chamise combustion particles).…”
Section: Composition and Morphologysupporting
confidence: 84%
“…The individual particles are composed of non-homogeneously mixed carbonaceous and inorganic materials. Chamise smoke particles are more fractal-like in nature, resembling the morphology typical for BC, diesel, or methane soot, while palmetto smoke particles are dominated by OC and inorganic species (Hopkins et al, 2007a). The particles are aggregates of the mixed materials, so that the exposed surface is composed of inorganic inclusions alongside carbonaceous species, as evident from the microscopy images of chamise combustion particles in Fig.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Saarikoski et al (2008) observed an OC/EC ratio of 6.6 for biomass burning and 0.71 for vehicular emissions, whereas Sandradewi et al (2008) found values of 7.3 and 1.1 for these two sources, respectively. Hopkins et al (2007) studied the particles emitted during combustion of several plant fuels at different temperatures and suggested that flaming conditions produce more EC and less OC while smoldering fires result in higher OC content. Regional air quality over the northwestern part of India during winter season is considerably influenced by the annual practice of crop harvesting.…”
Section: Wintermentioning
confidence: 99%
“…The SOM-derived composition of ASOP implies their inherent relevance to atmospheric brown carbon and their plausible contribution to the absorption and scattering of solar and terrestrial radiation 19 . Estimates of ASOP optical properties based on reported correlations 20 with the O/C ratio and the sp 2 hybridization suggest values of single scattering albedo of 0.8-1.0 and Ångström absorption coefficients of 1.5-3.5-characteristic of brown carbon, respectively. Dynamic environmental SEM imaging of hydrating ASOP ( Supplementary Fig.…”
mentioning
confidence: 99%